A Guide for Inflatable Penile Prosthesis Reservoir Placement: Pertinent Anatomical Measurements of the Retropubic Space. (1st January 2014) - Henry, Gerard; Hsaio, Wayland; Karpman, Edward; Bella, Anthony T.; Carrion, Rafael; Jones, Leroy; Christine, Brian; Eisenhart, Elizabeth; Cleves, Mario A.; Kramer, Andrew
Abstract: Introduction: The primary concern for many prosthetic urologic surgeons in placing the three-piece inflatable penile prosthesis (IPP) is the concept of "blind reservoir placement." Extensive reports permeate the literature regarding bladder, bowel, vascular, and various hernial complications occurring while attempting to place the reservoir into the retropubic space. However, despite these widely documented complications, there is a paucity of published literature on surgically pertinent anatomical measurements of the retropubic space relating to reservoir placement. The focus of this project was to evaluate the special relationships and anatomical measurements of the retropubic space to better aid the surgeon in the safe placement of the reservoir. Aim: Analyses of the spatial measurements of reservoir placement into the retropubic space with a focus on utilizing a penoscrotal approach were conducted. In addition, we reviewed and evaluated the published literature for important contributions surrounding the various surgical techniques during placement of a penile prosthesis reservoir. Methods: Cadaveric pelvic specimens were dissected to determine the distance and angulation (in degrees) from the inguinal ring to several critical anatomic structures in the pelvis. This format was utilized to simulate the basic features of reservoir placement into the classic retropubic space. We also reviewed and evaluated the published literature for important contributions describing the various surgical techniques in the placement of penile prosthesis reservoirs into the retropubic space. Main Outcome Measures: Anatomic measurements were obtained from the inguinal ring to the bladder, external iliac vein, and superior origin of the dorsal suspensory ligament at the anterior apex of the pendulous penis. The angle was measured from the inguinal ring to these structures and recorded. We also reviewed the published literature for various penoscrotal IPP surgical techniques involving placement of the reservoir into the retropubic space to further supplement the pertinent spatial relationships data acquired in this study. Results: Of the 28 cadavers, 3 were excluded because of signs of major pelvic surgery, and an additional 6 sides were excluded because of unilateral fibrosis/surgery or difficulty in exposure. Distance to the decompressed bladder was 5–8 cm (average 6.45 cm) at a 15–30 (22.8) degrees medial measurement from the inguinal ring. The filled bladder was 2–4 cm (average 2.61 cm) from the inguinal ring. The external iliac vein distance from the inguinal ring was 2.5–4 cm (average 3.23 cm) at a 20–60 (36.4) degrees lateral measurement from the inguinal ring. Heretofore, the published literature does not appear to have detailed measurements that are provided in this study. Conclusions: These anatomical measurements of the retropubic space demonstrate the importance of decompressing the bladder and avoiding deep dissection lateral to the inguinal ring, as the external iliac vein is much closer than currently espoused. We feel that these data are significant to the surgeon proceeding with reservoir placement during IPP surgery.